THE INFLUENCE OF ORGANIZATIONAL CULTURE AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE (CASE STUDY BPJS EMPLOYMENT PEKANBARU CITY) - Hardiansyah, Muhammad Untung; Jer, Abdul Razak; Nugroho, Gilang (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
ABSTRACTThis research aims to test the analysis of organizational culture factors and leadership style through job satisfaction as an intervening variable on the performance of BPJS Employment Employees in Pekanbaru City. The analytical technique used to analyze the effects of intervening variables is the path analysis method, with several tests carried out, including, validity test, reliability test, descriptive analysis, classic tests which include multicollinearity tests, autocorrelation tests, heteroscedasticity tests, and normality tests. The population and sample in this research were 162 BPJS Employment employees in Pekanbaru City. The results of the path analysis prove that Organizational Culture has an indirect positive and significant influence on the Performance of BPJS Employment Employees in Pekanbaru City which is mediated by Job Satisfaction. This is evident from the results of the t test where the t-count of 2.164 for Organizational Culture is greater than the t-table of 1.990. Meanwhile, Leadership Style has an indirect positive and significant influence on the Performance of BPJS Employment Employees in Pekanbaru City which is mediated by Job Satisfaction. This is evident from the results of the t test where the t-count of 2.103 for Leadership Style is greater than the t-table of 1.990. Keywords :Organizational culture; Leadership Style; Job satisfaction; Employee Performance